1977
DOI: 10.1002/cpt1977224430
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of [3H]‐vincristine in man

Abstract: The pharmacokinetics, metabolism, and excretion of aromatically labeled tritiated vincristine (VCR) was examined in 4 patients. Clearance of radioactivity from the blood was triphasic with half-life t1/2 values of 0.85, 7.4, and 164 min. The initial phases probably represent distribution and binding to formed blood elements which exceeded 50% of the administered dose by 20 min. Excretion of radioactivity was principally fecal, with 33% recovered in the feces by 24 hr and 69% by 72 hr. Considerably less radioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
28
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(34 citation statements)
references
References 0 publications
5
28
1
Order By: Relevance
“…The VCR concentrations used in the present study are in line with clinically obtained data (Bender et al, 1977;Jackson et al, 1981;Van Tellingen et al, 1992) and with earlier described cytotoxic concentrations in vitro (Jackson & Bender, 1979;Ferguson et al, 1984).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The VCR concentrations used in the present study are in line with clinically obtained data (Bender et al, 1977;Jackson et al, 1981;Van Tellingen et al, 1992) and with earlier described cytotoxic concentrations in vitro (Jackson & Bender, 1979;Ferguson et al, 1984).…”
Section: Discussionsupporting
confidence: 90%
“…It is given by intravenous bolus injection. No long-lasting therapeutic levels are achieved in this way (Bender et al, 1977). However, more frequent administration of VCR is not feasible, because its use is limited by the occurrence of peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, it is uncertain whether such variability in drug exposure results in a similar variability in antileukemic effect. We confirmed that vincristine disposition in children is characterized by a long terminal t 1/2 ␤ and a large Vd ss , as has been reported in adults (16,17,37,38). A long t 1/2 ␤ and a large Vd ss suggest avid tissue binding.…”
Section: Discussionsupporting
confidence: 89%
“…It was found that urinary excretion accounts for up to 12% of excreted radioactivity (16,17). The biliary system appeared to be the principal route of excretion (13, 18 -20).…”
mentioning
confidence: 99%
“…The peak blood concentrations that occur with conventional chemotherapeutic dose schedules may be looked at. There are studies on patients undergoing chemotherapy in which the peak plasma concentrations ofMTX (Chabner, 1979), AD (Tattersall et al, 1975), BLM, (Teale et al, 1977), VCR (Bender et al, 1977) and HU (Belt et al, 1980) are, albeit transiently within an order of magnitude of the concentrations of these agents which we found optimally enhanced BeWo hCG production in vitro. Obviously intra-tumour drug levels will differ from plasma levels, but the studies referred to do at least indicate that the optimum in vitro concentrations are not wildly different from those that occur in patients receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 53%